AB1071 Antiphospholipid Syndrome Alliance for Clinical Trials and International Networking (APS Action) Core Laboratory Validation Exercise: Comparison of Chemiluminescence Immunoassay (CIA) and Enzyme-Linked Immunosorbant Assay (ELISA). (9th June 2015) - Bertolaccini, M.L.; Willis, R.; Lakos, G.; Andrade, D.; Pengo, V.; Banzato, A.; Krilis, S.; Erkan, D.
Abstract : Background: APS ACTION International Clinical Database and Repository was created to study the natural course of disease over 10 years in persistently aPL-positive patients with/without other systemic autoimmune diseases. The protocol involves testing for anticardiolipin antibodies (aCL) and anti-β2glycoprotein I antibodies (aβ2GPI) at five different international core laboratories in samples collected at multiple sites. Although all core laboratories use the same ELISA kits, APS ACTION core laboratory directors agreed that an exchange of samples to assess intra- and inter-laboratory variability is crucial to establish whether an acceptable agreement among the core labs can be achieved. As part of the this validation exercise, two different assays were used. Objectives: To assess between-laboratory agreement obtained with a novel antiphospholipid (aPL) chemiluminescence immunoassay (CIA), and compare the results to those obtained with ELISA assays. Methods: Blinded serum samples from aPL positive patients and controls (n=30) were distributed to the five APS ACTION core laboratories. All samples were tested for IgG, IgM and IgA aCL and aβ2GPI with the FDA cleared QUANTA Flash® CIA and QUANTA Lite® ELISA kits (Inova Diagnostics). For every sample, the average, SD and %CV of the values were calculated. Between laboratory precision was considered acceptable if %CV was less than 20%. Results: Categorical agreement between the two methods was 100%, 97% and 77% for IgG, IgM and IgA aCL, respectively, and 87%, 93% and 77% for IgG, IgM and IgA ab2GPI, respectively. The correlation between quantitative results was good (Spearman rho 0.917, 0.809 and 0.893 for IgG, IgM and IgA aCL, respectively; rho 0.938, 0.766 and 0.78 for IgG, IgM and IgA anti-b2GPI. All p values <0.0001). Only CIA met the <20% total CV acceptance criteria for all the samples with all the assays. %CV was higher for ELISA and, in some cases, well outside the acceptable range (Table ). Conclusions: IgG and IgM aCL and aβ2GPI results showed good agreement between CIA and ELISA. Agreement was lower for IgA assays due to borderline samples being positive for CIA (a very sensitive test) and negative for the ELISA. Based on the evaluations performed in the APS ACTION Core Laboratories, CIA and ELISA tests displayed substantially equivalent performance for the detection of aCL and aβ2GPI. QUANTA Flash® CIA, a fully automated assay, however, showed higher level of reproducibility, making inter-laboratory comparisons more reliable. Disclosure of Interest: M. L. Bertolaccini: None declared, R. Willis: None declared, G. Lakos Employee of: Inova Diagnostics Inc, D. Andrade: None declared, V. Pengo: None declared, A. Banzato: None declared, S. Krilis: None declared, D. Erkan: None declared